Immunization of Male Rabbits with Pseudomonas aeruginosa Increases Spermatogenesis (World Journal of Experimental Biosciences, 2015)
The impact of immunity on spermatogenesis is documented in the literature. This study highlighted the influence of Pseudomonas aeruginosa hyper-immunization on male rabbit testicular spermatogenesis as the effect of immune response on sex hormones changes. Morphometric criteria were used to evaluate spermatogenesis. The level of hormone was estimated by enzyme-linked immunosorbent assay (ELISA). We found that male rabbits vaccinated with the bacteria showed a highly significant (P<0.001) decreased in spermatogonia cell number (11.46±8.11 in test vs 45.19±10.76 in control). In addition there was a significant increase (P<0.001) in spermatocytes cell number represented by pachytene and zygotene cells in vaccinated animal as compared to control (88.5±8.11 in test vs 54.14±10.13 in control). In concomitance with these changes, there was a significant elevation in level of testosterone in immunized groups (3.55±3.86 in test vs 0.98±0.8 in control). While, no significant change was observed in progesterone (2.00±0.80 in test vs 1.83±0.79 in control) and estradiol (21.42±14.02 in test vs 19.31±3.72 in control) levels. The histopathological changes included detachment of spermatogonia in the test group was observed. The increase in spermatogenesis and the changes in hormones level as well as histopathological changes suggest that the immune mechanisms impact spermatogenesis in males rabbits.